INORGANIC GEOCHEMISTRY OF THE OIL OF WEST SIBERIA: FIRST ICP-MS DATA - Fedorov Y.N.; Ivanov K.S.; Erokhin Y.V.; Ronkin Y.L. (My University, 2007)
The evolution in innovation technologies and analytical devices has raised geochemistry to a higher level. As is known, modern petroleum geochemistry is mainly composed of organic geochemistry. The trace element composition of oils was studied usually in combustion products, whereas works on direct determination of the trace element composition of hydrocarbons are scanty and generally related to a very small number of elements and/or heavy fractions. The rapid progress in the method of mass spectrometry with inductively coupled plasma (ICP-MS) has made it possible to study the trace element composition of not only rocks, but also complex organic compounds, for instance, oil and its derivatives. A series of works has recently been reported on the geochemistry of asphaltenes and bitumens, i.e., solid components of oil. We analyzed for the first time the trace element composition of crude oil from West Siberia by the ICP-MS method.